The water mite family Mideopsidae (Acari: Hydrachnidia): a contribution to the diversity in the Afrotropical region and taxonomic changes above species level - Pešić, Vladimir; Cook, David; Gerecke, Reinhard; Smit, Harry (Zootaxa, 2013)
A rearrangement of genera and subgenera in the water mite family Mideopsidae is proposed, resulting in the following changes: Mideopsellinae Lundblad, 1937 and Phreatomideopsinae Schwoerbel, 1986 are synonymized with Mideopsidae Koenike, 1910; Djeboa K. Viets, 1911, Mideopsides Lundblad, 1943, Neoxystonotus Lundblad, 1927, Octomideopsis K. Viets, 1931 and Xystonotus Wolcott, 1900 are redefined and proposed as distinct genera. A global key for the genera of the family is given.        New records of water mites of the genus Djeboa K. Viets, 1911, Xystonotus Wolcott, 1900 and Mideopsellides K.O.Viets, 1962 (Acari: Hydrachnidia, Mideopsidae) from the Afrotropical region are presented. Twenty species new to science are described, i.e., Djeboa amendano (Madagascar), D. amethystica (Madagascar), D. angulipalpis (Madagascar), D. coelestinica (Madagascar), D. crocodilorum (South Africa), D. curtipalpis (Ghana), Djeboa depressa (Côte d’Ivoire), D. dinosaurophila (South Africa), D. elephantina (Côte d’Ivoire), D. ghanaensis (Ghana), D. gledhilli (Côte d’Ivoire, Ghana), D. globulipalpis (South Africa, Ghana), D. granatica (Madagascar), D. mandena (Madagascar), D. maromandia (Madagascar), D. nzia (Côte d’Ivoire), D. turmalinica (Madagascar), D. vanilla (Madagascar), D. wondergemi (Ghana) and Xystonotus madagascariensis (Madagascar); a first description of the male is given for Djeboa bimaculata (Cook, 1966). A key for all species of the Djeboa is presented.